Peran Teknologi Keuangan: Perspektif Gen-Z tentang Penggunaan E-Banking dan Dompet Digital - Andi Hidayat; Dwi Andini Nur Hasanah; Nadya Laviana; Annisa Sri Wijaya (Jurnal Manajemen dan Bisnis Kreatif)
This research aims to measure perspectives regarding differences in financial technology users between e-banking and digital wallets as well as convenience for Gen Z. The object of this research is in the city of Makassar with the research subjects being Generation-Z, with a sample of 100 respondents. The data collection technique was carried out using a research questionnaire distributed to respondents, with data analysis techniques using paired sample test analysis with the JASP application. Research findings show that there is no difference in terms of the perspective of using financial technology with e-banking or digital wallets among generation-Z in Makassar City